Influence of genetic polymorphisms of styrene-metabolizing enzymes on the levels of urinary biomarkers of styrene exposure. Issue 2 (4th March 2015) - Carbonari, Damiano; Mansi, Antonella; Proietto, Anna Rita; Paci, Enrico; Bonanni, Rossana Claudia; Gherardi, Monica; Gatto, Maria Pia; Sisto, Renata; Tranfo, Giovanna
Graphical abstract